2017
DOI: 10.11604/pamj.2017.28.8.13097
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis and HIV infections among pregnant women attending antenatal clinics in Republic of Congo

Abstract: IntroductionHIV and syphilis during pregnancy remain a public health concern especially in developing countries. Pregnant women attending antenatal clinics sites for the first time between September and December 2011 and who accepted to participate in the study were enrolled. The objective was to estimate the syphilis and HIV infection rate in this population.MethodsA study was conducted in 44 selected ANCs from 12 departments (5 urban and 7 rural). Pregnant women who accepted to participate in the study, atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 15 publications
10
13
1
1
Order By: Relevance
“…This is similar to the previous study conducted in Rwanda among pregnant women attending ANC where syphilis prevalence was 2.0% [8]. Also our finding are in accordance with previous study conducted in Democratic Republic of Congo where HIV infection rate was estimated to be 3.6% [12]. Furthermore, the observed HIV prevalence of 4.2% and syphilis of 1.2% in this study are consistent with the study conducted at Gondar, Ethiopia 4.1% and 1.9% respectively [13].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is similar to the previous study conducted in Rwanda among pregnant women attending ANC where syphilis prevalence was 2.0% [8]. Also our finding are in accordance with previous study conducted in Democratic Republic of Congo where HIV infection rate was estimated to be 3.6% [12]. Furthermore, the observed HIV prevalence of 4.2% and syphilis of 1.2% in this study are consistent with the study conducted at Gondar, Ethiopia 4.1% and 1.9% respectively [13].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with study conducted in Tanzania where higher prevalence were found in the young age group [16]. Also, it is in accordance with Roch Fabien Niama et al, where in their finding, age group above 25 year of age had increased risk of infection than others [12]. This may be attributed to the increased risk of exposure to STIs, since this age group is very sexually active [13] In this study, a bigger proportion of HIV and syphilis positivity were seen in cohabitant women compared to the married women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Syphilis is an emerging STD that has been growing in recent years especially among people with HIV. Syphilis and HIV appear to be the most commonly reported STDs [67]. Some studies have shown that the prevalence of syphilis among women is increasing worldwide [68].…”
Section: Discussionmentioning
confidence: 99%
“…The co-infection of sexually transmitted infections and HIV may be having a profound detrimental effect especially among the youth in developing countries. Syphilis and HIV appear to be the most reported STIs, although there has been a worldwide decrease in the prevalence of syphilis by the year 2000 [2].…”
Section: Introductionmentioning
confidence: 99%